A cost-benefit analysis of implementing a 54 MW solar PV plant in a South African platinum mining company: A case study - Barnard, S.S.S.; Smit, A.M.; Middelberg, S.L.; Botha, M.J. (Journal of Energy in Southern Africa, 2021)
A reliable and secure supply of energy is a prerequisite for adequate output and economic growth – especially in a platinum mining company. With exponential tariff increases, inadequate power supply leading to power cuts, and a carbon tax introduction, this study compared the costs with benefits by implementing a 54 MW solar photovoltaic (PV) plant. Two scenarios were compared over the same 20-year period in a case study of a South African platinum mining company operating in the platinum belt of Rustenburg. The first scenario was grounded upon the decision to proceed with the conventional manner of sourcing electricity from Eskom, South Africa’s power utility. The second scenario assessed the implementation of a 54 MW solar PV plant. The findings reveal that the company could generate 2 439 753 MWh of clean energy over 20 years with an investment of ZAR 910 857 920, giving a ZAR 563 205 994 (11%) carbon tax saving and a ZAR 5 614 426 335 (10%) reduction in electricity costs. Further, installing the solar PV plant could reinforce the company‘s dedication to protecting the environment and creating job opportunities through the employment of staff to install and maintain the plant.